Respuesta :
Answer:
1 and 4 has same pairs of solution.
Step-by-step explanation:
Solutions for the given equations are:
[tex]1. (x+6)(x - 6) = 0\\(x+6) = 0, (x-6) = 0\\x = -6, x = 6\\\\2. (x + 6)(x + 6) = 0\\(x+6) = 0, (x+6) = 0\\x = -6, x = -6\\\\3. (x - 6)(x - 6) = 0\\(x-6) = 0, (x-6) = 0\\x = 6, x = 6\\\\4. (2x + 12)(2x - 12) = 0\\(2x+12) = 0, (2x-12) = 0\\x = -6, x = 6\\\\5. (2x - 12)(x - 12) = 0\\(2x-12) = 0, (x-12) = 0\\x = 6, x = 12\\\\6. (x+12)(x - 12) = 0\\(x+12) = 0, (x-12) = 0\\x = -12, x = 12\\\\7. (x +12)(x-6) = 0\\(x+12) = 0, (x-6) = 0\\x = -12, x = 6[/tex]
(x+6)(x - 6) = 0 and (2x + 12)(2x - 12) = 0 have same pair of solutions.